Transformation of the discipline "Concepts of Modern Natural Science" for the development of critical thinking - M. V. Solodikhina (Russian State Vocational Pedagogical University, 2023)
Introduction. Globally, there are integrated natural science disciplines in the training programmes for humanities students in many universities in order to overcome the gap between the humanitarian-artistic and natural-science cultures, to form a holistic view of the physical world and the basics of technology among university graduates, to equip them with the scientific method of cognition. In Russia, such a discipline is "Concepts of Modern Natural Science". However, in its current form, it does not fully meet the abovementioned goals. Due to the lack of a practical line, students do not master the skills of applying the scientific method and do not get an idea about science as a tool for understanding nature and a way of thinking, but instead they become stronger in the perception of natural science as a storehouse of ready-made true knowledge. Nevertheless, the situation changes if the focus is shifted from the transfer of knowledge to the development of critical thinking, which in most countries of the world is recognised as the main goal of university education.   Aim. The present research aims to identify the structure, content and types of training tasks of the course "Concepts of Modern Natural Science", contributing to the development of critical thinking of students in the humanities, and the corresponding transformation of the course "Concepts of Modern Natural Science".   Methodology and research methods. The identification of the optimal structure, content and types of training tasks, as well as the evaluation of the results of the introduction of the transformed course "Concepts of Modern Natural Science" into the educational process were carried out on the basis of research conducted at two universities - RUDN University and Moscow State Pedagogical University. The tests were applied to assess the structure of motivation, natural science knowledge and critical thinking skills, tests of epistemological ideas. Also, the authors used the surveys showing students' perception of the effectiveness of teaching methods and means, the usefulness of natural science knowledge and critical thinking for study, life, self-development and professional activities.   Results. It is shown that students and teachers have a positive attitude towards the idea of making critical thinking the main goal of studying the course "Concepts of Modern Natural Science". The change in goal-setting makes it possible to connect natural science and the humanities through critical thinking as a means of understanding nature and man, to introduce a practical line that includes tasks-simulators of critical thinking skills and the application of the scientific method and projects in the implementation of which these skills become tools of knowledge. After studying the transformed course "Concepts of Modern Natural Science", the motivation of students to study natural science, their epistemological ideas, cognitive skills and assimilation of natural science material improved.   Scientific novelty. A course structure was developed with two integration centres; additions were made to the course content that contribute to the development of students' epistemological ideas and the conscious formation of cognitive skills; a practical line was introduced, consisting of tasks that require the use of certain cognitive skills in the study of problem situations in accordance with the stages of the scientific method; the procedural component of the course was complemented by methods for the development of thinking.   Practical significance. The created case-practice is variable and can be applied in the practical line ofany integrated natural science discipline.